2021
DOI: 10.30658/jicrcr.4.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Managing COVID-19 Pandemic Crisis: The Case of Greece

Abstract: This qualitative study analyzes the Greek government’s crisis management practice and public communication efforts during two waves of the COVID-19 pandemic in 2020. Integrating both crisis management theories and the World Health Organization’s pandemic control plans, discourse analysis and case study approaches were taken to analyze how Greek’s key government and public health authorities communicated with the public using different frames and crisis response strategies. Evaluations were conducted to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“… 96 To communicate these risks, the government of Greece featured 2 leaders during COVID-19 press briefings, a professor focused on the medical developments and a secretary who communicated governmental decisions and crisis management measures. 97 This approach resembled the way that Singaporean officials “spoke with one voice” during the SARS epidemic 48 and contributed to similar public satisfaction with governmental leadership during these epidemics. 98 , 99 These examples suggest that political will and commitments are foundational for the actions necessary to facilitate social and behavioral change.…”
Section: Lessons Learned #5: Cultivate Political Will and Commitmentmentioning
confidence: 96%
See 1 more Smart Citation
“… 96 To communicate these risks, the government of Greece featured 2 leaders during COVID-19 press briefings, a professor focused on the medical developments and a secretary who communicated governmental decisions and crisis management measures. 97 This approach resembled the way that Singaporean officials “spoke with one voice” during the SARS epidemic 48 and contributed to similar public satisfaction with governmental leadership during these epidemics. 98 , 99 These examples suggest that political will and commitments are foundational for the actions necessary to facilitate social and behavioral change.…”
Section: Lessons Learned #5: Cultivate Political Will and Commitmentmentioning
confidence: 96%
“…96 To communicate these risks, the government of Greece featured 2 leaders during COVID-19 press briefings, a professor focused on the medical developments and a secretary who communicated governmental decisions and crisis management measures. 97 This approach resembled the way that Singaporean officials "spoke with one voice" during the SARS epidemic 48 and contributed to similar public satisfaction…”
Section: Lessons Learned #5: Cultivate Political Will and Commitmentmentioning
confidence: 96%
“…By calculating the speech acts and modality features of the texts, they revealed the institutional power and the social relationships underlying the SARS notice discourse (Zhang and Pan, 2015). In a qualitative study of Greece’s response to COVID-19 during two waves of infections, Aspriadis (2021) analysed the Greek government’s official website pages using methods from political discourse analysis. The study identified coherent strategies among three leading authoritative figures who rhetorically framed national response to the crisis as war and individual social responsibility in the earlier wave of the pandemic (Aspriadis, 2021).…”
Section: Previous Work and The Interpretative Model For The Current S...mentioning
confidence: 99%
“…In a qualitative study of Greece’s response to COVID-19 during two waves of infections, Aspriadis (2021) analysed the Greek government’s official website pages using methods from political discourse analysis. The study identified coherent strategies among three leading authoritative figures who rhetorically framed national response to the crisis as war and individual social responsibility in the earlier wave of the pandemic (Aspriadis, 2021). Such framing strategies were slightly altered in the second wave with greater prominence of the individual social responsibility frame and a hope frame adopted alongside risk-heightening and image-bolstering strategies (ibid.…”
Section: Previous Work and The Interpretative Model For The Current S...mentioning
confidence: 99%
See 1 more Smart Citation